Wnt1 Promotes EAAT2 Expression and Mediates the Protective Effects of Astrocytes on Dopaminergic Cells in Parkinson's Disease. (9th September 2019) - Wei, Lei; Chen, Chuan; Ding, Li; Mo, Mingshu; Zou, Jing; Lu, Zhenze; Li, Haiyan; Wu, Haotian; Dai, Yongqiang; Xu, Pingyi; Lu, Zhengqi
Abstract : Background . Wnt/ β -catenin signaling has been reported to exert cytoprotective effects in a cellular model of Parkinson's disease (PD). Glutamate excitotoxicity has been suggested to contribute to the pathogenesis of PD, and excitatory amino acid transporters (EAATs) play a predominant role in clearing excessive glutamate. EAAT2 is mainly expressed in astrocytes, which are an important source of Wnt signaling in the brain. Methods . Wnt1-overexpressing U251 astrocytes were indirectly cocultured with dopaminergic SH-SY5Y cells treated with 6-hydroxydopamine (6-OHDA). Cell toxicity was determined by cell viability and flow cytometric detection. Glutamate level in the culture medium was determined by enzyme-linked immunosorbent assay (ELISA). Western blot analysis was used to detect the expression of Wnt1, β -catenin, and EAAT2. Immunofluorescence was used to display the expression and translocation of NF- κ B p65. Results . 6-OHDA treatment significantly decreased cell viability in both U251 cells and SH-SY5Y cells, inhibited the expression of Wnt1, β -catenin, and EAAT2 in U251 cells, and increased the glutamate level in the culture medium. Coculture with Wnt1-overexpressing U251 cells attenuated 6-OHDA-induced apoptosis in SH-SY5Y cells. Overexpression of Wnt1 decreased the glutamate level in the culture media, upregulated β -catenin, EAAT2, and NF- κ B levels, and promoted the translocation of NF- κ B from the cytoplasm to the nucleus in U251 cells. Conclusion . Wnt1 promoted EAAT2 expression and mediated the cytoprotective effects of astrocytes on dopaminergic cells. NF- κ B might be involved in the regulation of EAAT2 by Wnt1.